Family Support in Use of Contraception in Coastal Slums Area in Medan, North Sumatra, Indonesia - Syafran Arrazy; Tri Bayu Purnama; Nofi Susanti; Yulia Khairina Ashar; Muhammad Ancha Sitorus; Desy Nuri Fajarningtiyas (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
The use of contraception can prevent the risk of death for both mother and infant due to unplanned pregnancy. This study measures adult women's knowledge, attitudes, and behavior in contraceptive use in coastal slums. Knowledge, attitudes, and behaviors are supported by supporting factors and driving factors at the mother's household level. This research used a multilevel analytical with a cross-sectional approach. Adult women (individual levels) and heads of the family (family level) are subject in this study, separated into two groups in the individual and household unit. The total sample in this study is 734 samples and originated from 374 samples in individual and household units. The results of this study indicate that maternal knowledge about contraception and mother's education has a positive effect on contraceptive use, as well as husband's support and economic status. Women with an elementary and junior high school education tend not to use contraception 3-5 times more than women with higher education.The family variation between environments binds 26% of the results to the existing multilevel analysis so that contributions made by intervening risk factors at the family level will increase participation in individual contraceptive use by 26%. Supporting factors for mothers in using contraception influence the support of their husbands and family support. Elementary and junior high school education still dominantly influence contraception in adult women in first and second models. Women with primary and junior secondary education tend not to use contraception three to five times more than the group of women who have higher education. Contributions that can be made by intervening risk factors at the family level will increase the participation of contraceptive use in individuals by twenty-six percent. Keywords: Contraception, Family Support, Slum Area.